Professional Ethics as A Moderator in the Relationship Between Knowledge Sharing, Experience, Obedience Pressure, And Audit Judgment - Wardhana, Rony; Anam, Saiful; Miftakhul Ivanda, Muhammad Nur (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: In this research, Knowledge Sharing, Experience, Obedience Pressure, and Professional Audit Ethics effect auditor judgment in Surabaya and Sidoarjo Public Accounting Firms (KAPs). It seeks to resolve contradictions in earlier research and increase empirical data on audit knowledge exchange. Methodology: The quantitative technique employed Partial Least Square-Structural Equation Modeling (PLS-SEM) using SmartPLS software. Purposive sampling chose 120 auditors from 15 KAPs with at least 2 years of audit experience and a bachelor's degree. Primary data was acquired using 5-point Likert scale questionnaires for all dimensions, including moderating effects. Findings: The investigation indicated that Knowledge Sharing, Experience, Obedience Pressure, and Professional Audit Ethics significantly influence Audit Judgment. Of the moderating factors examined, only one had a meaningful impact on the connection between the variables and Audit Judgment. The research affirms the significance of these characteristics in formulating good audit judgments and supports the perspective that robust knowledge-sharing channels, with expertise, ethical commitment, and adherence to regulations, improve the quality of auditors' conclusions. Originality/value: This paper is original Paper type: a Research Paper